PRELIMINARY REVISIONS OF SOME GENERA OF MALAYSIAN PAPILIONACEAE I - M. S. VAN MEEUWEN; H. P. NOOTEBOOM; C.G.G.J VAN STEENIS (REINWARDTIA, 1961)
The revisions have been performed by Miss M. S. van Meeuwen (Pycnospora, Smithia, Uraria), H. P. Nooteboom (Galactia, Moghania, Rhynehosia, Stylosanthes, Zornia), and C. G. G. J. van Steenis (Cyclocarpa, Neocollettia).